Evaluation of clonazepam-induced teratogenesis on embryonic day 16 (ED16) mallard duck (Anas platyrhynchos) embryos - BALANGAT, JULIE ANNE (Archīum Ateneo, 2017)
Existing literature regarding the teratologic potential of clonazepam during the later stages of development is limited. This study therefore aimed to characterize toxic effects of clonazepam on ED16 mallard duck (Anas platyrhynchos) embryos. Nine groups each with nine eggs (n=81; three viable eggs per treatment with three replicates) were used in the present study. Eight groups were treated with 50L of the following: (1) saline (0.85%), (2) vitamin C 54g/mL (VC), (3) clonazepam 11g/mL (C11), (4) clonazepam 32g/mL (C32), (5) clonazepam 54g/mL (C54), (6) clonazepam 75g/mL (C75), (7) C75+VC, and (8) dimethyl sulfoxide (DMSO). One group was left untreated. Data were analyzed using GraphPad Prism 6 at P.0.0001, P.0.001, P.0.01, and P.0.05 significance levels. Based on the results, clonazepam may (but not significantly) lower survival rates and embryo weights, and may promote growth retardation (compared with the control groups) and embryo disintegration. At lower concentrations, clonazepam induces the formation of smaller eyes [C11 vs. saline (P.0.05) and VC (P.0.0001)], shorter upper limbs [C11 vs. C32 (P.0.05)], and shorter beaks [C11 (P.0.01) and C54 (P.0.05) vs. VC]. Exposure to clonazepam may also induce immunologic and hyperemic responses (observed in heart tissues). Liver and heart weight, and histology sections of the liver were unaffected by clonazepam exposure. VC pre-treatment among C75 embryos did not show improvements in mean values of all parameters tested. Results therefore show that clonazepam is not a strong teratogen in mallard duck embryos (Anas platyrhynchos). However, risk for morphological anomalies, though substantially low, cannot be excluded.